Combination chemotherapy of ifosfamide, 5-fluorouracil, etoposide and cisplatin as perioperative treatment in lymph node positive bladder carcinoma patients treated by radical cystectomy - Komai, Yoshinobu; Fujii, Yasuhisa; Okubo, Yuhei; Yamamoto, Shinya; Kawakami, Satoru; Yonese, Junji; Fukui, Iwao (International journal of urology, 2008)
Objectives:  To evaluate the efficacy and toxicity of perioperative combination chemotherapy with ifosfamide, 5‐fluorouracil, etoposide and cisplatin (IFEP) in bladder cancer patients with regional lymph node metastases treated by radical cystectomy. Methods:  We reviewed the medical records of 183 consecutive patients who underwent radical cystectomy for invasive urothelial carcinoma of the bladder. Of those, 26 patients with regional lymph node metastasis who were regarded as being rendered surgically disease‐free (pT1‐4, N1‐2, cM0) and treated with perioperative IFEP chemotherapy were the subjects of the present study. Results:  Median follow‐up of 26 patients was 49 months (range 4–150). Grade 3 and 4 bone marrow toxicities were seen in 15 and four patients, respectively. Neither chemotherapy‐related death nor febrile neutropenia occurred. The 5‐year overall and cancer‐specific survival rate was 60% and 68%, respectively. The overall survival rate of the patients with pT4 disease was significantly worse than that of patients with pT1‐3. There were four N2 patients who survived for over 5 years free of disease. Conclusions:  Perioperative IFEP therapy appeared to be effective in the treatment of lymph node positive bladder cancer patients who underwent radical cystectomy. Further study may be warranted.